Right hemisphere dysfunction and metaphor comprehension in young adults with Asperger syndrome. - Gold R; Faust M (Journal of Autism & Developmental Disorders, 2010)
This study examined whether the known difficulties in metaphor comprehension exhibited by persons with Asperger syndrome (AS) can be explained by a dysfunctional right hemisphere (RH). Using the divided visual field paradigm, 27 AS participants and 36 matched controls were presented with word pairs of four types (literal, conventional metaphors, novel metaphors, and unrelated word pairs), and were asked to perform a semantic judgment task. The main hypothesis was that whereas the control group participants will show RH superiority for novel metaphor processing, no RH superiority will be found in the AS group. Results indeed indicate much less RH contribution to novel metaphor comprehension in AS, and are discussed in light of linguistic models and the neurobiology of autism.